PERSPEKTIF SISWA SEKOLAH DASAR TERHADAP PEMBERIAN PR DALAM KURIKULUM MERDEKA - Manuhutu, Godwin; Jani, Lauren; Thome, Bunga; Kalinggoru, Elshy; Lomi Ratu, Aldi; Ghitu, Maria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the perceptions of fifth-grade students in Maulafa Subdistrict, Sikumana Village, Kupang City regarding homework within the framework of the Merdeka Curriculum, which emphasizes autonomy, meaningful learning, and student-centered instruction. Employing a qualitative descriptive design, data were collected through semi-structured interviews involving five students and two classroom teacher. The findings indicate that students generally perceive homework as instrumental in strengthening conceptual understanding and maintaining learning continuity outside school hours. However, certain subjects particularly mathematics are identified as sources of difficulty, whereas language-related assignments are considered more manageable and engaging. Students also demonstrate a preference for homework that involves written tasks, book-based responses, and collaborative work, reflecting alignment with the curriculum’s emphasis on learning independence and social learning. The teacher’s perspective further supports the relevance of homework, provided that assignments remain proportional, clear, and directly connected to classroom instruction. The study concludes that homework retains pedagogical significance in the Merdeka Curriculum era, although its design requires careful calibration to ensure it remains supportive, non-burdensome, and conducive to fostering student motivation and responsibility.